The effect of contact lens wear on tear immunoglobulins - (:unkn) unknown (My University, 1991)
We assayed tear immunoglobulins (IgA, IgG, and IgM) by radial immunodiffusion in 24 contact lens wearers and 22 healthy control subjects. IgA level was found to be increased (P ≤ 0.02) in rigid contact lens wearers (mean: 0.14 ± 0.07 g/L) compared to control subjects (mean: 0.08 ± 0.06 g/L). IgA levels of both of PMMA contact lens wearers (mean: 0.14 ± 0.08 g/L; P ≤ 0.05) and rigid gas permeable contact lens wearers (mean: 0.13 ± 0.07 g/L; P ≤ 0.05) were increased in comparison with the control group. No statistically significant differences were found in IgA levels of various types of soft contact lens wearers or in IgG or IgM levels between wearers and controls. The mean duration of lens wear was 6.4 years (range: 1-20 years), and an increase in IgG level was found, related length of lens wear (P ≤ 0.03). We believe that the continuous mechanical stimulation of conjunctiva alters the level of tear immunoglobulins, especially the IgA type.